Influenza A (H5N1) Viruses from Pigs, Indonesia - Nidom, Chairul A.; Takano, Ryo; Yamada, Shinya; Sakai-Tagawa, Yuko; Daulay, Syafril; Aswadi, Didi; Suzuki, Takashi; Suzuki, Yasuo; Shinya, Kyoko; Iwatsuki-Horimoto, Kiyoko; Muramoto, Yukiko; Kawaoka, Yoshihiro (Emerging infectious diseases, 2010)
Pigs have long been considered potential intermediate hosts in which avian influenza viruses can adapt to humans. To determine whether this potential exists for pigs in Indonesia, we conducted surveillance during 2005-2009. We found that 52 pigs in 4 provinces were infected during 2005-2007 but not 2008-2009. Phylogenetic analysis showed that the viruses had been introduced into the pig population in Indonesia on at least 3 occasions. One isolate had acquired the ability to recognize a human-type receptor. No infected pig had influenza-like symptoms, indicating that influenza A (H5N1) viruses can replicate undetected for prolonged periods, facilitating avian virus adaptation to mammalian hosts. Our data suggest that pigs are at risk for infection during outbreaks of influenza virus A (H5N1) and can serve as intermediate hosts in which this avian virus can adapt to mammals.